GENDER DIFFERENCES IN LANGUAGE TEACHING AND THEIR PEDAGOGICAL IMPLICATIONS - Gafforov Khasan (Social science and innovation, 2023)
This article analyzes the gender differences of language learners in learning foreign languages and the influence of these gender characteristics on the educational process. The article explores the human factor-centered approach to the study of language phenomena, its features and peculiarities in linguistic research in gender studies. The task of developing, improving, and optimizing methods of teaching foreign languages taking into account gender differences has been one of the most urgent problems of our national education system, and this article analyzes these problems of the education system from the point of view of pedagogical importance.